Sarah A. James, Hellenistic Pottery. The Fine Wares, Corinth 7, 7. - Erickson , Brice (Journal of Hellenistic Pottery and Material Culture, 2019)
In the latest publication of the Corinth excavations, Sarah James draws on new evidence from deposits in the Panayia Field east of the Forum to construct a new account of the development of Corinthian fine wares in the 3rd and 2nd cent. BCE. This account seeks to redress issues left unresolved or in need of correction in the canonical study of Corinthian Hellenistic pottery presented by G. Roger Edwards. J.’s focus is narrower in the sense that she deals exclusively with Corinthian fine wares and leaves out imported fine wares and the local cooking and coarse pottery that was also included in the earlier work. In another sense, the scope is significantly more expansive, for it reviews all the older material on which Edwards’s chronology was based and adds to this a detailed study of six unpublished deposits.